1999
DOI: 10.1016/s0008-6363(98)00340-x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor antagonists prevent neointimal proliferation in a porcine coronary artery organ culture model

Abstract: Direct blockade of AngII receptors effectively inhibits cell proliferation and restenosis post-angioplasty in vitro. ACE inhibition, exclusive of flow, does not attenuate proliferative restenosis. These data suggest that AngII contributes to neointimal proliferation and validates the concept that receptor antagonists could contribute to the therapeutic management of restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 59 publications
5
30
0
Order By: Relevance
“…These data were further supported by an ANG II-dependent increase in the nuclear localization of PCNA, which was blocked with either an AT 1 or AT 2 receptor subtype antagonist (Fig. 4), in agreement with our previous examination of bromodeoxyuridine incorporation (26).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These data were further supported by an ANG II-dependent increase in the nuclear localization of PCNA, which was blocked with either an AT 1 or AT 2 receptor subtype antagonist (Fig. 4), in agreement with our previous examination of bromodeoxyuridine incorporation (26).…”
Section: Resultssupporting
confidence: 92%
“…This study confirms our previous observation that neointimal formation in porcine coronary artery rings could be inhibited by PD-123319 as well as losartan following balloon-catheter injury in vitro (26). Furthermore, we have previously shown that ANG II-induced neointimal formation involves two events, cell proliferation and cell migration (14,28,29).…”
Section: Discussionsupporting
confidence: 91%
“…This result suggested a basal activation of AT1 receptors through intracellular angiotensin II production (Kumar et al 2007). This finding was not surprising, as a number of researchers have demonstrated that the local production of angiotensin II by smooth muscle cells is sufficient to mediate restenosis (Wilson et al 1999). In summary, these data confirm that angiotensin II plays a central role in the pathophysiology of cardiovascular diseases via the AT1 receptor by modulating the rate of growth.…”
Section: Discussionsupporting
confidence: 63%
“…This assumption has been confirmed by organ culture studies using porcine coronary artery. Incubation of porcine coronary artery segments with FBS in vitro results in the development of a neointima associated with a compact extracellular matrix and few disruptions in the internal elastic lamina (10). In this organ culture model of coronary restenosis, because the inhibition of angiotensin II receptors effectively inhibits cell proliferation and restenosis post-angioplasty in vitro, it is suggested that angiotensin II contributes to neointimal proliferation and validates the concept that receptor antagonists could contribute to the therapeutic management of restenosis.…”
Section: -3 Other Proliferative Agentssupporting
confidence: 57%